Stop forgetting to remember the autobiography of Walter Kurtz - Kuper, Peter 1958- (Crown Publishers, 2007)
The fictional autobiography of the author's alter ego Walter Kurtz focuses on the life-changing arrival of his first child as he deals with the challenges of parenthood, a quarrel with his best friend, and the events of September 11th